The philosophical and ethical dimensions of artificial intelligence in the Olympic Movement - Lagos, Iasson (Πανεπιστήμιο Πελοποννήσου, 2025)
This thesis explores the ethical and philosophical implications of Artificial Intelligence (AI) within the Olympic Movement. It focuses on the compatibility of the utilization of AI with Olympism’s principles of respect, friendship and excellence. This thesis analyzes how AI could be integrated into the Olympic Movement through a qualitative desk-based research methodology. The research highlights the capacity of AI to help improve decision-making, reduce human error, foster equitable competition by leveraging data-driven insights, and allow for a more precise management of events and governance. Despite the potential benefits, the study identifies ethical challenges associated with the use of AI, including algorithmic bias, privacy concerns, and the diminishing role of human agency in sports. The research underscores the importance of transparency, accountability, and fairness in AI applications, emphasizing the need for robust ethical oversight to prevent the unregulated use of AI from undermining the values central to the Olympic Movement. Philosophical considerations focus on maintaining a balance between technological innovation and preserving the humanistic values in sports. To address these challenges, the thesis highlights the need for a framework to govern the use of AI within the Olympic context while taking into account ethical considerations. It recommends the establishment of an AI Ethics Charter, including, among others, equitable access to AI technologies and ethical education for athletes, coaches, and officials. By fostering ethical AI practices aligned with the principles of Olympism, the Olympic Movement can embrace technological advancements while preserving its core values. The study concludes that ethical AI governance is essential to ensuring that the use of AI serves as a force for good, enhancing inclusivity and fairness while maintaining the integrity and spirit of the Olympic Games.
Keywords: Τεχνητή νοημοσύνη - Ηθικές απόψεις; Ολυμπιακό κίνημα; Ολυμπιακές αξίες; Ολυμπισμός; Τεχνητή νοημοσύνη - Φιλοσοφία; Artificial intelligence - Moral and ethical aspects; Olympic movement; Olympic Values; Olympism; Artificial intelligence - Philosophy; Artificial Inteligence; Olympic Movement; Olympic Values